Inherited Cardiac Arrhythmia Syndromes: Focus on Molecular Mechanisms Underlying TRPM4 Channelopathies - Mohamed-Yassine Amarouch; Jaouad El Hilaly (Cardiovascular Therapeutics)
The Transient Receptor Potential Melastatin 4 (TRPM4) is a transmembrane N-glycosylated ion channel that belongs to the large family of TRP proteins. It has an equal permeability to Na+ and K+ and is activated via an increase of the intracellular calcium concentration and membrane depolarization. Due to its wide distribution, TRPM4 dysfunction has been linked with several pathophysiological processes, including inherited cardiac arrhythmias. Many pathogenic variants of the TRPM4 gene have been identified in patients with different forms of cardiac disorders such as conduction defects, Brugada syndrome, and congenital long QT syndrome. At the cellular level, these variants induce either gain- or loss-of-function of TRPM4 channels for similar clinical phenotypes. However, the molecular mechanisms associating these functional alterations to the clinical phenotypes remain poorly understood. The main objective of this article is to review the major cardiac TRPM4 channelopathies and recent advances regarding their genetic background and the underlying molecular mechanisms.